หลักแห่งการปกครองตนเองตามเจตนารมณ์ของประชาชนในท้องถิ่นในระบบกฎหมายของสภายุโรป - Thatsaringkharnsakun, Uthen (Journal of Community Development Research (Humanities and Social Sciences); Vol 14 No 2 (2021): April - June 2021DO - 10.14456/jcdr-hs.2021.20, 2021)
การศึกษาถึงหลักแห่งการปกครองตนเองตามเจตนารมณ์ของประชาชนในท้องถิ่น ซึ่งเป็นหลักพื้นฐานที่สำคัญในกฎบัตรยุโรปว่าด้วยการปกครองตนเองส่วนท้องถิ่นของสภายุโรปมีวัตถุประสงค์ดังนี้ 1) ศึกษาถึงวิวัฒนาการของกฎบัตรยุโรป 2) ศึกษาถึงเนื้อหาของมาตรการทางกฎหมายที่บัญญัติไว้ในกฎบัตรยุโรป และ 3) ศึกษาถึงการนำเอากฎบัตรยุโรปไปบังคับใช้กับประเทศสมาชิกของสภายุโรป ในการศึกษานี้ใช้ระเบียบวิธีการศึกษาแบบวิจัยทางเอกสาร      ผลการศึกษา พบว่า 1) หลักแห่งการปกครองตนเองตามเจตนารมณ์ของประชาชนในท้องถิ่น หรือที่รู้จักกันเป็นสากลในชื่อว่า หลักแห่งการปกครองตนเองส่วนท้องถิ่น ได้ปรากฎขึ้นให้เห็นอย่างชัดเจนนับตั้งแต่ในสมัยกลางของยุโรปที่พระมหากษัตริย์ได้มอบกฎบัตรให้แก่หน่วยการปกครองส่วนท้องถิ่น เพื่อให้ความอิสระบางประการในการปกครองตนเอง และได้วิวัฒนาการมาสู่การจัดทำเอกสารที่สำคัญ เช่น กฎบัตรยุโรปว่าด้วยเสรีภาพขององค์กรปกครองส่วนท้องถิ่นในปี ค.ศ. 1953 ปฏิญญาว่าด้วยหลักความอิสระของท้องถิ่นในปี ค.ศ. 1968 และการจัดทำกฎบัตรยุโรปว่าด้วยการปกครองตนเองส่วนท้องถิ่นในปี ค.ศ. 1985 ซึ่งมีสถานะเป็นสนธิสัญญาที่มีผลผูกพันตามกฎหมายระหว่างประเทศ 2) เนื้อหาของมาตรการทางกฎหมายที่สำคัญในกฎบัตรยุโรปที่เกี่ยวข้องกับองค์กรปกครองส่วนท้องถิ่นประกอบด้วยเรื่องต่างๆ เช่น การสร้างการคุ้มครองทางกฎหมายของหลักแห่งการกครองตนเองส่วนท้องถิ่น แนวความคิดและขอบเขตของหลักการปกครองตนเองส่วนท้องถิ่น โครงสร้างการบริหารงานและทรัพยากรที่เหมาะสมกับภารกิจ ตลอดจนสิทธิในการรวมกลุ่มเป็นสมาคมขององค์กรปกครองส่วนท้องถิ่น เป็นต้น 3) การบังคับใช้กฎบัตรในประเทศสมาชิก ได้แก่ เดนมาร์ก สเปน และเนเธอร์แลนด์ พบว่า ปัญหาสำคัญ ที่ดำรงอยู่ในระบบกฎหมายการปกครองส่วนท้องถิ่นของประเทศเหล่านี้ เช่น ปัญหายังไม่มีการคุ้มครองหลักการปกครองตนเองส่วนท้องถิ่นในระบบกฎหมาย ปัญหาการกำหนดและจัดสรรภารกิจที่ไม่ชัดเจนและซ้ำซ้อนให้แก่องค์กรปกครองส่วนท้องถิ่น ปัญหาการขาดแคลนทรัพยากรทางการเงิน และปัญหาการกำกับดูแลที่เข้มงวดเกินไป เป็นต้น และข้อเสนอแนะคือการนำเอามาตรการทางกฎหมายดังที่บัญญัติไว้ในกฎบัตรมาบัญญัติไว้ในรัฐธรรมนูญหรือกฎหมายภายในของรัฐสมาชิกเพื่อให้มีการบังคับใช้อย่างแท้จริง คำสำคัญ : การปกครองส่วนท้องถิ่น  การปกครองตนเองส่วนท้องถิ่น  เจตนารมณ์ของประชาชนในท้องถิ่น  สภายุโรป      The study of the principle of self-government according to the will of the local people which is an important basis in the European Charter of Local Self-Government of the Council of Europe has three objectives as follows: 1) Studying the evolution of the European Charter, 2) Studying the content of legal measures as defined in the European Charter and 3) Studying the application of the European Charter in the member States of the Council of Europe. This study uses the methodology of documentary research.      The results of the study revealed that: 1) The principle of self-government according to the will of the people in the locality, known internationally as the principle of local self-government clearly existed since the Middle Ages of Europe that the monarch granted the Charters to the local government units to provide some autonomy for their self-government which later it evolved into the preparation of important documents such as the European Charter of Municipal Liberties of 1953, the Declaration of Principles on Local Autonomy of 1968 and developed into the arrangement of the European Charter of Local Self-Government in 1985 which has a treaty status binding on international law; 2) The content of important legal measures in the European Charter relating to local government consists of matters such as the legal protection of local self-government, the concepts and scope of local self-government, the appropriate administrative structures and resources for tasks as well as the right to associate; 3) The application of Charter in member States, namely Denmark, Netherlands and Spain, found that the main problems that exist in the local government system of these member States, such as there is no legal protection for the principle of local self-government in the legal system, the problems of assigning and allocating ambiguous and redundant tasks for local authorities, the problems of inadequate financial resources for local authorities to perform the tasks as well as the problem of administrative supervision on local authorities that are too strict, etc.; 4) The suggestion is to bring legal measures as stipulated in the Charter into the constitution or the internal law of the member States in order to be truly enforced. Keywords: Local Government, Local Self-Government, The Will of the People in the Locality, Council of Europe